Corporate investment and stock market valuation - Shushu Liao; Marco Errico (Journal of Business Finance & Accounting, 2022)
We study the driving forces behind the positive association observed between corporate investment and stock market valuation, and how they interact with managerial equity incentives and informativeness of investment. We build a dynamic model where managers use investment choices to influence investors' opinions about firms' future prospects and increase the market valuation. The incentives to manipulate the valuation processes increase with managerial equity incentives and informativeness of investment. Our empirical findings support the model's predictions that the tendency of using investment to boost market valuation is stronger when managerial stock ownership is high or when earnings quality is low (i.e., there is strong reliance on investment for information).
Keywords: 650; compensation; equity incentives; executives; financial report quality; investment; investment informativeness; misvaluation; stock market; top management team